Investissement culturel, Energie langagière et traduction du Texte Sacré (Séminaire international sur la traduction du langage religieux à SUCEAVA – ROUMANIE, 2008)

(untitled) - Said Khadraoui (Séminaire international sur la traduction du langage religieux à SUCEAVA – ROUMANIE)
The topic of our communication is a sort of personal reflection about the notion of translation applied on sacred writings. Our main preoccupation is to emphasize an important aspect which is the problem of translation methods. From this, it seems that a redefinition of translation applied on sacred writings has been imposed from the angle of operational notions: cultural investment and language energy that we find in the fundamental practices of literary writing. From this perspective, the main problem is the interpretation of foreign signs by a reader without being confronted to a connotation made by a translation with a controversial identity.